Anthropogenic impact on erosion, pedogenesis and fluvial processes in the central European landscapes of the eastern Harz mountains forelands (Germany). (1st March 2023) - Dreibrodt, Stefan; Langan, Carolin C.M.; Fuchs, Markus; Bork, Hans-Rudolf
Abstract: The Holocene development of soils and sediments at three sites in the eastern Harz foreland was investigated using field and laboratory methods and integrated into the regional Holocene record of this central European landscape. Apart from early Holocene processes, the history of mid-to late Holocene slope erosion was found to be closely linked to the local land-use history. By c. 1000 BP, soil erosion is a process that is detectable throughout the study area. The studied Chernozemic soils that now cover large areas of the studied landscape are of varying Holocene age. Linear radiocarbon age-depth relations of soil organic matter and indicative changes in soil mineral composition suggest that the Chernozem was formed by long-lasting anecic earthworm cast accumulation at the soil surface. Persistent periods of landscape openness maintained by local preindustrial agriculture explain the promotion of anecic earthworms in naturally forested landscapes of central Europe and act as temporally transgressive drivers of landscape change. An early to mid-Holocene phase of reduced fluvial activity was followed by the onset of Holocene flooding, which correlates with the onset of mining in the Harz Mountains around ca. 3000 BP (e.g. Helme). The onset of flooding of the small streams Zapfenbach and Liethe coincided with the documented medieval and modern mining phases in the eastern Harz. At all sites, present-day flooding frequencies are higher than during the early to mid-Holocene. Shifts in river system behaviour attributable to anthropogenic activities in the Harz Mountains are therefore considered another Anthropocene marker. Based on our observations, we propose that land-use-induced alteration of central European low Mountain rivers and the formation of Holocene Chernozems in subhumid central Europe, in addition to anthropogenic-induced Holocene soil erosion, are included in the cadastre of early Anthropocene processes. These processes have left distinct traces in the continental geologic record. Thus, they would support arguments for long-term time transgressive anthropogenic transformation of Earth surface systems. However, the tipping points for these processes are dated differently (soil erosion - ca. 1000 BP, river activity - ca. 3000 BP, Chernozem formation - diachronous since the Neolithic) and are closely linked to local and regional land use history. Thus, our results are another example that the definition of "golden spikes" remains a critical undertaking, especially for the beginning of the Anthropocene. Highlights: Central European Holocene soil erosion, soil formation, and low mountain river activity are "Anthropocene" processes. Tipping points of these geosystems vary in age and are related to local and regional land use history. Holocene formation of central European Chernozems can be explained by anecic earthworm excretions.